Discrepancy in Uses and Gratifications for Smartphone and their Effects on Online Socialization Patterns among University Youth - Saeed, Robina; Hussain, Mudassar; Tariq, Anam (Annals of Human and Social Sciences, 2024)
The objectives are to explain the effects of political, business, educational, religious, communication, companionship, social interaction, passing time, escapist, relaxation, and entertainment uses and gratifications for smartphone (independent variables) use on online socialization patterns (dependent variable). Current study is done with the background of uses and gratifications in context of smartphone use to explain the increasing online socialization and less offline communication. By using quota sampling technique university students are selected from the four provinces of Pakistan (N = 763) through online questionnaire. The social interaction uses and gratifications for smartphone use make the strongest contribution to the virtual socialization patterns. However, the educational motives uses and gratifications do not significantly predict the virtual socialization patterns. It is suggested to teachers to use smartphone as a tool in pedagogy with caution.